Optimization of key ingredient levels in gluten-free rice bread by response surface methodology - Clavecilla, Jeleen Parreno; Dumelod, Benelyn Domingo (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
In response to the need for gluten-free (GF) food items for people with gluten-related diseases, this study was conducted to determine the optimum levels of water (W) and xanthan gum (X) in GF rice bread from local rice varieties, using response surface methodology (RSM). The rice flour ratio for the working formulation was set at 34% IMS5 (waxy) to 64% NSIC Rc122 (non-waxy), based on consumer acceptance test (n=50). The range of input variables W and X were 74.39 to 95.61% flour weight basis (fwb) and 0.53 to 3.07% fwb, respectively. The indicators %CV, Model P-value and agreement between the adjusted and predicted R2 showed that the objective response variables water activity (Aw), loaf height and specific volume and the sensory response variables apparent air cell size (AACS), moistness, stickiness, initial bite compactness (IBC), firmness and crumbliness were significantly affected by the input variables. Water level had a positive effect on Aw (P<0.0001), loaf height (P<0.0001), specific volume (P<0.0001), AACS (P<0.0001), moistness (P<0.0001), stickiness (P<0.0001), IBC (P<0.05) and crumbliness (P<0.0001) while its effect on firmness (P<0.0001) was negative. Xanthan gum level had a positive effect on IBC (P<0.001) and firmness (P<0.001), and a negative effect on Aw (P<0.05), loaf height (P<0.05), specific volume (P<0.05), AACS (P<0.0001), stickiness (P<0.05) and crumbliness (P<0.001). Significant interactions between W and X occurred in the models for Aw, loaf height, specific volume, AACS, stickiness, IBC, firmness and crumbliness while quadratic terms were also present for Aw and AACS. Numerical optimization showed that 88.09% fwb W and 1.85% fwb X were the most desirable combination based on GF bread quality parameters. The predicted optimum met AACS but not firmness and crumbliness of the reference commercial loaf bread.
Thesis Classification: C
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Bread